2021
DOI: 10.1038/s41467-020-20350-6
|View full text |Cite
|
Sign up to set email alerts
|

Light quantum control of persisting Higgs modes in iron-based superconductors

Abstract: The Higgs mechanism, i.e., spontaneous symmetry breaking of the quantum vacuum, is a cross-disciplinary principle, universal for understanding dark energy, antimatter and quantum materials, from superconductivity to magnetism. Unlike one-band superconductors (SCs), a conceptually distinct Higgs amplitude mode can arise in multi-band, unconventional superconductors  via strong interband Coulomb interaction, but is yet to be accessed. Here we discover such hybrid Higgs mode and demonstrate its quantum control by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 39 publications
1
40
0
Order By: Relevance
“…41 ). The experimental scheme has been extended to d-wave cuprate superconductors 42,43 and multiband superconductors 44,45 . Here we investigated THz-THG in FeSe 0.5 Te 0.5 to extract the dynamics of the superconducting order parameter upon the photoexcitation.…”
Section: Resultsmentioning
confidence: 99%
“…41 ). The experimental scheme has been extended to d-wave cuprate superconductors 42,43 and multiband superconductors 44,45 . Here we investigated THz-THG in FeSe 0.5 Te 0.5 to extract the dynamics of the superconducting order parameter upon the photoexcitation.…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that purely electronic processes in iron-based superconductors with strong interband Coulomb coupling lead to a controllable hybrid-Higgs collective mode. This mode was observed as THz four-wave-mixing signal coherent oscillations, whose field and temperature dependences are clearly distinguished from those observed in single-band or weakly-coupled multi-band superconductors 21 .…”
mentioning
confidence: 75%
“…superconducting states requires quantum sensing of their collective modes and underlying order parameters. Such characterization is challenging with ultrafast PP THz spectroscopy [20][21][22][23] . First, the collective excitations of superconducting states couple linearly to electromagnetic fields only in the presence of a finite Cooper-pair center-of-mass momentum p S .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Symmetry-driven physical phenomena, such as second harmonic generation and topological non-trivial properties are only a sliver of the applications for new NCS materials. [1][2][3][4][5][6][7][8][9] Ternary silicon phosphides, such as Ba 2 Si 3 P 6 , MnSiP 2 , and RuSi 4 P 4 have shown promising nonlinear optical properties, [10][11][12][13][14] and have prompted the investigation of other metal tetrel pnictides. [15] Generally, NCS structures are rare in intermetallics (< 10 %) but are much more prevalent (up to 95 %) among transition metal silicon phosphides where M/(Si + P) < 1.…”
Section: Introductionmentioning
confidence: 99%